2013
DOI: 10.15381/rpb.v20i3.5202
|View full text |Cite
|
Sign up to set email alerts
|

Agrotransformación y evaluación de la resistencia a Phytophthora infestansen Solanum tuberosum L. variedad Désirée

Abstract: El Oomiceto Phytophthora infestans (Mont.) de Bary, agente causal de la enfermedad denominada tizón tardío, es el principal responsable del déficit en rendimiento y producción en el cultivo de papa a nivel mundial; una de las alternativas a considerar en la lucha contra este patógeno es la integración de secuencias completas de genesRen el genoma de la papa a través de Agrotransformación. El gen Rpi-blb2(gen R) de la especie silvestre Solanum bulbocastanum Dunal,presenta una amplia resistencia a los aislam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The Rpi-blb2 gene isolated from S. bulbocastanum (wild potatoes in Mexico) was transformed to cv. "Desiree" via agro-infection and it conferred high resistance against the late blight disease in the transgenics with high dose inoculation of two isolates of P. infestans to the entire transgenic plant, demonstrated by the unsuccessful reinoculation event of P. infestans in the transgenic potatoes (Orbegozo et al, 2016). With the use of the oxalate oxidase 4 gene (Osoxo4) isolated from rice overexpressed and transformed in S. tuberosum L. cvr Chipsona 3 via Agrobacterium mediated transformation under the regulation of 35S promoter, elevated activity of the enzyme oxalate oxidase was demonstrated in the transgenic potatoes with higher level of reactive oxygen H 2 O 2 .…”
Section: Phytophthora and Verticillium Resistant Potatoesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rpi-blb2 gene isolated from S. bulbocastanum (wild potatoes in Mexico) was transformed to cv. "Desiree" via agro-infection and it conferred high resistance against the late blight disease in the transgenics with high dose inoculation of two isolates of P. infestans to the entire transgenic plant, demonstrated by the unsuccessful reinoculation event of P. infestans in the transgenic potatoes (Orbegozo et al, 2016). With the use of the oxalate oxidase 4 gene (Osoxo4) isolated from rice overexpressed and transformed in S. tuberosum L. cvr Chipsona 3 via Agrobacterium mediated transformation under the regulation of 35S promoter, elevated activity of the enzyme oxalate oxidase was demonstrated in the transgenic potatoes with higher level of reactive oxygen H 2 O 2 .…”
Section: Phytophthora and Verticillium Resistant Potatoesmentioning
confidence: 99%
“…The transgenic potato lines exhibited immunity against both PVX and PVY (Bai et al, 2009). Orbegozo et al (2016) reported development of transgenic potatoes cv. "Desiree" resistant against Potato leafroll virus (PLRV) using self-excisable Cre-LoxP in vector that contained inverted repeats of CP gene under the control of heat inducible promoter and nptII as selection marker.…”
Section: Potatoes With Virus Resistancementioning
confidence: 99%